KEMAMPUAN PENGENALAN GEOMETRI MELALUI KEGIATAN BERMAIN BALOK ANAK USIA 5-6 TAHUN - Lathipah Hasanah; Shinta Agung (Journal of Early Childhood Education (JECE), 2019)
The purpose of this research is to improve the ability of introduction of geometry in the 5 to 6 year old children  through blocks playing activities. The subject of this research is children in grade B, RA Al-Watoniyah 16 Rawa Terate Cakung, East Jakarta. The method uses classroom action research. This research uses qualitative and quantitative approach according to Kemmis model which consists of four stages: planning, action, observation and reflection. The average score obtained in pre intervention is  35.90%. Based on these results, interventions must be taken through blocks playing activities. After doing intervention in cycle I, the results obtain an average score of 61.52%. Then intervention in cycle II obtains an average score of 80.97%. Based on the results of research that has been implemented, blocks playing activities can improve the ability children to introduction geometry effectively. Furthermore, this activity also can improve the moral, cognitive, social emotional, language and motor development.